Treatment of erythrocytes with the 2-cys peroxiredoxin inhibitor, Conoidin A, prevents the growth of Plasmodium falciparum and enhances parasite sensitivity to chloroquine. - Mariana Brizuela; Hong Ming Huang; Clare Smith; Gaetan Burgio; Simon J Foote; Brendan J McMorran (PLoS ONE)
The human erythrocyte contains an abundance of the thiol-dependant peroxidase Peroxiredoxin-2 (Prx2), which protects the cell from the pro-oxidant environment it encounters during its 120 days of life in the blood stream. In malarial infections, the Plasmodium parasite invades red cells and imports Prx2 during intraerythrocytic development, presumably to supplement in its own degradation of peroxides generated during cell metabolism, especially hemoglobin (Hb) digestion. Here we demonstrate that an irreversible Prx2 inhibitor, Conoidin A (2,3-bis(bromomethyl)-1,4-dioxide-quinoxaline; BBMQ), has potent cytocidal activity against cultured P. falciparum. Parasite growth was also inhibited in red cells that were treated with BBMQ and then washed prior to parasite infection. These cells remained susceptible to merozoite invasion, but failed to support normal intraerythrocytic development. In addition the potency of chloroquine (CQ), an antimalarial drug that prevents the detoxification of Hb-derived heme, was significantly enhanced in the presence of BBMQ. CQ IC50 values decreased an order of magnitude when parasites were either co-incubated with BBMQ, or introduced into BBMQ-pretreated cells; these effects were equivalent for both drug-resistant and drug-sensitive parasite lines. Together these results indicate that treatment of red cells with BBMQ renders them incapable of supporting parasite growth and increases parasite sensitivity to CQ. We also propose that molecules such as BBMQ that target host cell proteins may constitute a novel host-directed therapeutic approach for treating malaria.